Observations of killer whales off East Antarctica, 82°-95°E, in 2009 - Olson, Paula A.; Ensor, Paul; Kuningas, Sanna (J. Cetacean Res. Manage., 2023)
Observations of killer whales (Orcinus orca) during a survey off East Antarctica, 82°–95°E revealed previously undescribed variations in pigmentation and group associations. During the survey 24 killer whale groups were sighted south of 60°S and classified, when possible, to Types A, B, or C based on their external morphology. Sufficient observation was available for nine groups to be classified: 2 groups of Type A; 1 mixed group of Type A and Type B; 3 groups of Type C; and 3 groups with eyepatch pigmentation intermediate in size between Types B and C. These whales may represent an intergrade between Types B and C or a previously unrecognised form. One of the ‘intermediate’ groups was observed feeding in a multi-species aggregation with other cetaceans in deep water. Clearly distinguishable Type A and Type B whales were observed feeding together in a mixed aggregation, the first time that this has been documented.